Model Pembelajaran PAI dengan Project Based Learning Berbasis ICT untuk Meningkatkan Kemampuan Berfikir Kritis Siswa SMA - Fadriati Fadriati; Litasari Muchlis; Iman Asroa BS (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Education in the 21st century requires students to have critical thinking skills, so they can improve their quality of life. The PAI learning model in high school requires an ICT-based Project Based Learning learning model to improve students' thinking skills, so they are able to solve problems. This study aims to produce a valid and practical ICT-based Project Based Learning model for PAI learning to improve high school students' critical thinking skills. Research questions formulated how to apply the Project Based Learning model based on ICT in learning? The research method used is the Research and Development method with the ADDIE model which includes stages; 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The results of the research and development of the PAI learning model with ICT-based Project Based Learning obtained an average validation result of 0.872 in the valid category and the results of the practicality test of 0.780 in the very practical category. Thus this model is valid and practical for use at the high school level.